(3GdGSJbUGA aj GdePgH aj TQM GdegPHs - (3VjGA GdOjf CHh YeQh YKeGf Hf YjSi Hf Ydj Hf OQjGS GdcQOi GdeGQGfis; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s ((3YHO GdYXje Hf aJhM Hf YHO Gddg GdeYQha HGHf GdeaUd s)
(3ChdgG (B:s
(3HGH UaI GdUdGI EPG CQGO Cf jUdi ai LeGYI s
(3BNQgG (B:s
(3aUd hEf jUdi ai HjJg Ch ai eSLO fLR GdLRA GdKGdK ef cJGH GdESJbUG ef GdePgH ai TQM GdegPH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs